KONSEP BIMBINGAN DAN KONSELING CLIEN CENTERED THERAPY ISLAMI UNTUK MENGURANGI KECEMASAN TERHADAP MASA DEPAN - ahkmad usman Affandi (AflahConsilia : Jurnal Bimbingan dan Konseling, 2022)
Client centerd therapy is a counseling technique where the most important role is the counselee himself, the counselee is left to find their own solutions to the problems they face. The relationship between counselor and counselee in the counseling process is no more than a partner. The counselor’s role is only as a driver and creator of situations that allow the counselee to develop on himself. Islamic client centerd therapy has essence is how the counselee feels that he is not alone because there is Allah SWT in all aspect of his life. This study uses a qualitaive research with a literature review approach. Data collection using various literacy both from journals, books, and other literature. The concept of Islamic guidance and counseling is to offer alternative solutions based on religious that are effective in reducing anxiety about the future. There are stages in this Islamic client centerd therapy, first creat comfortable conditions for the counselee so that he feels comfortable to remove anxiety. Second, the counselor assures that counsele is not alone there is Allah SWT is great listener and know everything. Third, make a future plans in wordly life such a career, family, social, and long term goals in the afterlife.